Side effects, adherence self-efficacy, and adherence to antiretroviral treatment: a mediation analysis in a Chinese sample. Issue 7 (2nd July 2016) - Zhang, Liying; Li, Xiaoming; Lin, Zhenping; Jacques-Tiura, Angela J.; Xu, Jinping; Zhou, Yuejiao; Qiao, Shan; Shen, Zhiyong; Stanton, Bonita
ABSTRACT: Antiretroviral therapy (ART) is a lifelong treatment. To date, ART adherence is suboptimal for most patients in resource-poor settings. Previous research indicates that medication side effects are perceived to be a significant barrier of high ART adherence. Data regarding the role of adherence self-efficacy in mediating the relationship between side effects from ART and adherence to ART are limited; thus, this study examines this potential mediational role of self-efficacy. A cross-sectional survey of 2987 people living with HIV aged ≥18 years was conducted in 2012–2013 in Guangxi Autonomous Region (Guangxi) which has one of the fastest-growing HIV rates in China. Of the total sample, 2146 (72.1%) participants had initiated ART. Participants reported the number of days of completing the daily dose of ART in the past month; adherence was defined as completing the daily dose at least 28 days in the last month (≥90%). Side effects were significantly negatively related to adherence to ART. Mediation analyses indicated that adherence self-efficacy significantly mediated the side effects–adherence relationship. Future interventions to increase adherence self-efficacy and effective coping with side effects among HIV patients are needed in order to improve their ART adherence.